The The Identity of Congrock 17 Semarang Group : Postcolonial Studies - Annisa Furi, Giza Abel; Utomo, Udi; Sunarto, Sunarto (Universitas Negeri Semarang, 2019)
The transformation of identity in the midst of high cultural pluralism is a problem for former colonized nations, such as Indonesia. The identity crisis that hit caused by the political identity factors which used to investigate the backgrounds and the debates on an identity formation. As a former colonized nation, Indonesia comes to a new kind of colonialization era that is no longer physical but mental colonialization. Postcolonial theory used to criticize the power of dominant cultures which help to analyze and build awareness of this crisis situation, namely through the concept of hybridity and mimicry which is used as a form of identity. The Congrock 17 Semarang group brings keroncong rock music as their form of identity which later gives them space to describe the position of Congrock 17 Semarang group.This study focused on the problem of the identity of Congrock 17 Semarang group and postcolonial studies. The problems are later outlined into 2 sub focuses, (1) What factors influence the selection of keroncong rock genre as their identity in terms of political identity phenomenon? (2) What are the results of the Congrock 17 Semarang identity in postcolonial studies? Research objectives (1) To understand the supporting factors of the Congrock 17 Semarang identity’s forming process in the political identity phenomenon (2) To analyze Congrock 17 Semarang identity in postcolonial studies. The writer used qualitative research methods. The writer also used several techniques to collect data such as, observation, interview and document studies. Data validation used triangulation technique. Data analysis carried out started from data reduction, data presentation, and drawing conclusions.The result of the research show that (1) Keroncong rock as the identity of congrock music 17 group was formed due to factors of media hegemony in carrying out the strategy of globalization. The media modernization continuous exposure in spreading rock at that time and in a long period of time become one of the strong factors in forming its identity. The social interaction occurs between congrock 17 group with communities in their environment also plays a major role in forming keroncong rock to reach its popularity at the moment. (2) Keroncong rock identity is formed through the unity of mimicry and hybridity to bring up the ambivalent behavior, which is imitating as well as resisting. Congrock 17 music work and performance was performed on stage shows the cultural identity unison between keroncong rock which if formed in third space. The implication given by the research on congrock 17 Semarang group is showing that keroncong rock hybrid identity can be the icon of music art to the communities, fellow musicians and the government in Semarang.